1933
DOI: 10.1084/jem.58.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Certain Spreading Factor Existing in Bacteria and Its Significance for Bacterial Invasiveness

Abstract: Invasive strains of staphylococcus and streptococcus contain a soluble factor which markedly increases tissue permeability and enhances the infections produced by these organisms, by other bacteria, and by vaccine virus as well. The non-invasive strains of the same species of staphylococci and streptococci do not contain this factor. The enhancing substance elaborated locally by organisms passes into the circulating blood and bringing about a general increase of tissue permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1935
1935
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(45 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…Consistent with this view, S. aureus hysA mutants exhibit a hypovirulent phenotype in models of acute pulmonary and cutaneous infection (22,23). In addition, hyaluronidases from numerous Gram-positive pathogens have been shown to promote tissue penetrance of bacteria, toxins, and large-molecular-mass dyes in the vicinity of the challenge site (25,57). In the present study, we employed a medical device-associated infection model to show that S. aureus-derived HysA is an important virulence factor within the context of chronic biofilm infection.…”
Section: Discussionmentioning
confidence: 82%
“…Consistent with this view, S. aureus hysA mutants exhibit a hypovirulent phenotype in models of acute pulmonary and cutaneous infection (22,23). In addition, hyaluronidases from numerous Gram-positive pathogens have been shown to promote tissue penetrance of bacteria, toxins, and large-molecular-mass dyes in the vicinity of the challenge site (25,57). In the present study, we employed a medical device-associated infection model to show that S. aureus-derived HysA is an important virulence factor within the context of chronic biofilm infection.…”
Section: Discussionmentioning
confidence: 82%
“…Duran-Reynals (1933) observed that culture extracts of S. aureus increased permeability of rabbit tissue to vaccinia virus, toxins and dyes. Subsequently, the 'spreading factor' was identified as a HL (Linker et al, 1955).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these strains of streptococcus contain the specific carbohydrate and are very active producers of the spreading factor. 2 years ago from an abscess in man. Both are very active in production of the spreading factor.…”
Section: Pneumococcus R Variant--this Was the Strain 1/192/r Obtaimentioning
confidence: 99%